کاریگەری مۆدێلێکی پێشنیازکراو پشت بەست بە فێربوونی ستراتیجی بۆ گەشەکردنی ئاڕاستە و بیرکردنەوەی شێوەیی لای خوێندکارانی پۆلی هەشتەمی بنەڕەتی لە بابەتی بیرکاری - محمد, سۆلاڤ فائق; محمد, ئاریان علی; کریم, بەفرین غریب غفور (Sulaimani Journal for Humanities, 2022)
This research aims to know the effectiveness of a proposed model based on strategic learning to develop direction and formal thinking among the students of the eighth grade basic in mathematics, the experimental method was used to reach the goal of research, where prepared the requirements of research such as the identification of scientific material, formulation of behavioral goals and preparation of the daily plan, and then the construction and preparation of the test (formal thinking and direction of mathematics). The test of formal thinking consists of (6) skills and (24) articles, and the direction test consisting of (4) dimensions and (28) options, after the assessing of trustworthiness and stability shows that both tests are high and acceptable. The experiment was applied to (69) students, experimental group (35) students and the controlled group (34) students of the eighth grade from (Shad) basic school for the studying year (2021-2022). The two groups were similar in terms of the age of students in months, a preliminary test of formal thinking and direction of mathematics, level of parental education, parental profession. The researcher taught the experimental group according to a proposed model based on strategic learning which includes eight steps (presentation of the objectives of the subject, identify important information, note recording, retrieval of associated information, step organization, material details, summarizing and monitoring understanding level, and control group in a traditional way. After the experiment, both the formal thinking test and the direction of the mathematics material were applied for both groups, and a set of statistical tools were used as Pearson Coefficient, Chi square, Mean or Median, Standard Deviation, T-Test by SPSS. The research found that there was a statistical difference in the level of significance (0.05) between the average score of the two groups of students to test formal thinking in favor of the experimental group, and between the average score of the two groups of students to the direction test in mathematics in favor of the experimental group. The research recommends using a proposed model based on strategic learning for the basic stage of mathematics, as well as training courses for math teachers for all stages to learn about formal thinking and skills.
Keywords: proposed model; strategic learning; formal thinking; direction for mathematics